Analisis Kemampuan Lahan Dan Penggunaan Lahan Di Kecamatan Lembah Gumanti Kabupaten Solok - Fitria, Mona Lisa (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
This study aims to: 1). Knowing the Land Capability in the District of Lembah Gumanti, Solok Regency. 2). Knowing the land use in Lembah Gumanti District, Solok Regency. 3). Knowing the relationship between land capability and land use in Lembah Gumanti District, Solok Regency. This type of research uses descriptive quantitative methods. The technique of collecting data by observing, measuring / direct observation and documentation. Sources of data from this study using primary data obtained and collected by researchers directly in the field and using secondary data obtained from journals and related agencies. The results of this study: 1). Valley Gumanti District has 3 classes of land capability, namely Class I, Class II and Class VI. Class I and Class II abilities are land that can be cultivated or agricultural and residential activities can be carried out, while for Class VI capabilities there are severe obstacles that make these lands unsuitable for agricultural use. Land use in Lembah Gumanti District consists of various types of land use, namely Dry Land Forest, Secondary, Settlement, Shrub Bush, Dry Land Agriculture, Rice Field and Lake. 3). The relationship between land capability and land use in Lembah Gumanti District is between class I land capability. Cultivation can still be done, such as the use of scrub land, secondary dry land forest, for land capability class VI, namely the use of secondary forest land where all the appearance of the forest has shown logging marks (the appearance of grooves and marks of logging). Severe logging but not included in HTI, Plantation or agricultural areas, it is better to leave the land use in this class because the land capability class in class VI has severe obstacles and cannot be cultivated. Keywords: Marriage, Fertility, Employment, Income